Analisis Perang Umat Islam dari Masa Nabi hingga Dinasti Abbasiyah: Dari Pertahanan Diri hingga Perang Saudara - Ghafrin, Zul; Syauqii, Fachri (Medan Resource Center, 2023)
This study analyzes the dynamics of wars that occurred in the history of the Islamic community, starting from the time of Prophet Muhammad to the Abbasid Dynasty. The study aims to understand how wars that initially focused on self-defense evolved into more complex internal conflicts, including civil wars. Using a historical and critical approach, this research explores the factors that drove this shift, including political, social, and religious influences. The findings of this study indicate that although the wars were initially motivated by the principle of defense against external threats, over time, various political interests and divisions within the Islamic community triggered internal conflicts, leading to civil wars. This research provides insights into the long-term impact of these conflicts on political and social developments in Islamic history.